2021
DOI: 10.3390/s21030903
|View full text |Cite
|
Sign up to set email alerts
|

Improving Resolution of Dual-Comb Gas Detection Using Periodic Spectrum Alignment Method

Abstract: Dual-comb spectroscopy has been an infusive spectroscopic tool for gas detection due to its high resolution, high sensitivity, and fast acquisition speed over a broad spectral range without any mechanical scanning components. However, the complexity and cost of high-performance dual-comb spectroscopy are still high for field-deployed applications. To solve this problem, we propose a simple frequency domain post-processing method by extracting the accurate position of a specific absorption line frame by frame. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Based on the time domain and frequency domain characteristics of the optical frequency comb itself, the application of the optical frequency comb has two main aspects. One is to provide a stable frequency reference, and the other is to serve as a high-precision light source in precision measurement [2][3][4][5][6]. Free-running optical frequency combs have large repetition frequency fluctuations under the interference of various noises, and cannot be directly used for various precise measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the time domain and frequency domain characteristics of the optical frequency comb itself, the application of the optical frequency comb has two main aspects. One is to provide a stable frequency reference, and the other is to serve as a high-precision light source in precision measurement [2][3][4][5][6]. Free-running optical frequency combs have large repetition frequency fluctuations under the interference of various noises, and cannot be directly used for various precise measurements.…”
Section: Introductionmentioning
confidence: 99%
“…OFC is one kind of coherent light source composed of a set of discrete frequency lines that were equally spaced forming a comb picture and the spacing frequency is usually in the radio-frequency (RF) domain 1 . Previous research has shown that OFC has great applications in microwave signal processing 2 , high-performance waveform synthesis 3 , coherent optical communication 4 , and gas detection 5 . In general, there are different setups for OFC generation such as ones based on mode-locked femtosecond lasers, resonators, or EOMs.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the NPR mode-locked fiber lasers include spatial light path part for polarization control and length adjustment [14][15][16][17][18], which puts forward strict requirement on precise collimation. Hence, this kind of laser can be easily interfered by environment.…”
Section: Introductionmentioning
confidence: 99%